Fundamentals of Pediatric Surgery Second Edition - Mattei, Peter; Nichol, Peter F.; Rollins, II, Michael D.; Muratore, Christopher S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The previous edition of this book was based on a simple but essential philosophy: provide a practical and up-to-date resource for the practicing surgeon detailing the specific needs and special considerations surrounding the surgical care of children. The second edition of Fundamentals of Pediatric Surgery stays true to the philosophy of the original with several significant enhancements. As well as encompassing the most up-to-date and practical clinical information for the experienced surgeon written in a straightforward narrative style, each chapter provides a rationale for the proposed approach based on the scientific evidence available in the literature and the author$1 (Bs personal clinical experience, supplies a detailed algorithm or clinical protocol in a graphic format, initiates a discussion regarding unanswered questions and proposals for future studies, and includes a list of suggested readings. Chapters cover in great detail a broad range of pediatric general surgery topics, including disorders of all major organ systems of the abdomen and thorax, congenital anomalies presenting in the newborn period, and a variety of maladies germane to the growing field of fetal surgery. The authors also provide authoritative discussions of therapeutic methods and surgical techniques that range from the traditional to the modern, including time-honored open operations, contemporary minimally invasive interventions, and emerging technologies such as single-site and robotic surgery. Written by experts in the field, Fundamentals of Pediatric Surgery, Second Edition is a definitive source of readily available clinical information that residents, fellows or attending surgeons can use to take care of actual patients in real time. .s
Preoperative Assessment and Preparation -- Prenatal Diagnosis and Genetic Counseling -- Epidural and Regional Anesthesia -- Enteral Nutrition and Access -- Parenteral Nutrition -- Enhanced Recovery Protocols -- Quality Improvement, Education, and Outcomes Research -- Shock -- Electrolyte Abnormalities -- Vascular Access -- Acute Kidney Injury -- Ventilation -- Extracorporeal Life Support -- Conjoined Twins -- Trauma Resuscitation -- Concussion -- Acute Head Trauma -- Neck Injuries -- Spine Trauma -- Burns -- Abdominal Trauma -- Thoracic Trauma -- Vascular Injury -- Hand Injuries -- Child Abuse -- The Critical Airway -- Bronchoscopy -- Benign Neck Masses -- Thyroid and Parathyroid Disease -- Esophageal Atresia and Tracheo-esophageal Fistula -- Long-Gap Esophageal Atresia -- Managing the Complex Esophagus -- Esophageal Injuries and Replacement -- Foregut Duplications -- Achalasia -- Persistent Ductus Arteriosus -- Vascular Compression Syndromes -- Congenital Lung Lesions -- Lung Biopsy and Resection -- Diseases of the Pleural Space -- Pectus Deformities -- Mediastinal Tumors -- Gastroesophageal Reflux Disease -- Hypertrophic Pyloric Stenosis -- Surgical Enteral Access -- Duodenal Atresia -- Intestinal Atresia -- Abdominal Cysts and Duplications -- Anomalies of Intestinal Rotation -- Necrotizing Enterocolitis -- Short Bowel Syndrome -- Meconium Ileus -- Intussusception -- Meckel$1 (Bs Diverticulum -- Bariatric Surgery -- Chronic Abdominal Pain -- Crohn$1 (Bs Disease -- Ileostomy and Colostomy -- Gastrointestinal Bleeding -- Enterocutaneous Fistula -- Constipation and Fecal Incontinence -- Hirschsprung Disease -- Perianal Disease -- Pilonidal Disease -- Appendicitis -- Ulcerative Colitis and Familial Polyposis -- Anorectal Malformations -- Gastroschisis -- Omphalocele -- Eventration of the Diaphragm -- Congenital Diaphragmatic Hernia -- Uncommon Hernias -- Umbilical Disorders -- Peritoneal Dialysis -- Ventricular Shunts for Hydrocephalus -- Disorders of the Abdominal Aorta and Major Branches -- Neonatal Hyperbilirubinemia -- Biliary Atresia -- Congenital Intrahepatic Cholestasis -- Cholecystitis -- Choledochal Cysts -- Hepatic Resection -- Portal Hypertension -- Congenital Hyperinsulinism -- Pancreatic Disorders -- Surgical Disorders of the Spleen -- Vesicoureteral Reflux -- Renal Abnormalities -- Penile Anomalies and Circumcision -- Inguinal Hernia and Hydrocele -- Undescended Testis -- Acute Scrotum -- Cloacal Exstrophy -- Disorders of Sex Development -- Vagina -- Neuroblastoma -- Wilms Tumor -- Adrenal Tumors -- Rhabdomyosarcoma -- Non-Rhabdomyosarcoma Soft-tissue Sarcoma -- Sacrococcygeal Teratoma -- Ovarian Tumors -- Testicular Tumors -- Liver Tumors -- Musculoskeletal Tumors -- Benign Skin Lesions -- Nevi and Malignant Melanoma -- Necrotizing Soft Tissue Infections -- Hemangiomas and Vascular Malformations -- Disorders of the Breast. .s
Keywords: Medicine; Surgery; Pediatric surgery; Medicine & Public Health; Pediatric surgery; General Surgery